Tipologi Integrasi Agama dan Ilmu Pengetahuan dalam Pemikiran Islam Kontemporer - Siti Badriah; Nanat Fatah Natsir; Erni Haryanti (Peneliti.net, 2021)
The dichotomy of religion and science is still firmly entrenched in the perception of society by considering it as something that cannot be reconciled. Contemporary Islamic thinkers try to make the concepts of science and religion into an integrated whole. The aim of this research is to analyze the typology of integration thinking, especially in Islamic educational institutions. The research method used is literature study. The results show a description of the typology concept in several typologies of thought that were developed by classifying them into several types, namely: IFIAS type, ASASI, Islamic Worldview, SPI, Scientific integration based on classical philosophy, Sufism and fiqh, Ijmali and Aligargh group types, Amin Abdullah and Interconnect Integration type developed by UIN.